"Comparación agronómica de dos métodos de nutrición de plantas en la producción de pimiento (capsicum annum), en el cantón Lomas de Sargentillo-Guayas". - Miranda Herrera, Felix Yair (2012)
The present investigation was carried out in the months from May to August 2011. It was done on the Property of Mr. Antonio Rodriguez, located in Canton Lomas de Sargentillo Canton in "Las Chacras" village 1.5km, Guayas Province. Its geographical location is: 1 º 52 '48''south latitude and 80 º 05' 13.3'' West longitude, located at a height of 35 meters above sea level, with an average temperature of 26 ° C, with a heliophany of 1600 hours per year, with an average annual rainfall of 500 mm, and 86% relative humidity. With the following objectives: To determine the efficiency of bio-based products in the production of pepper. To establish the connection between benefit/cost of the treatments used in this crop. To evaluate two methods of plant nutrition in crop production of pepper. To evaluate the efficiency of chemical and organic fertilizers in the cultivation of pepper, the hybrid Quetzal; were established 8 treatments with fertilizers, of which 4 were organic fertilizers such as Algasoil, Bioabor NBO, Caboron and the other 4 remaining were chemical fertilizers like ammonium sulfate, calcium nitrate, DAP and the witness farmer which was constituted by urea. Experimental design was used "randomized complete block" with cluster 4 x 4 in 3 repetitions; the variables were subjected to the analysis of variance, the Duncan test at 95% probability. From the experimental analysis results, we conclude that, most plant height at 30 days after transplantation was achieved with treatment 1000cc/ha NBO, while most plant height at 60 and 90 days were obtained with treatment ammonium sulfate (SAM) 250kg ha¯¹. While the greatest weight was obtained by treating calcium nitrate 250kg/ha and 350kg ha¯¹, Algasoil treatment. Averages are larger diameter, length, fruits per plant, performance and application of NBO enraizador humificado 1000cc ha¯¹, higher than average economic profit per hectare.